Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $B_t$ be a Wiener Process, then $U_t=B_t-tB_1,~0\le t \le 1$ is a Brownian bridge.

Show that $X_t=(1+t)U_{{t}/({1+t})}$ is a Wiener Process. I'm not quite sure how to start this off.

Any help would be greatly appreciated.

share|cite|improve this question
What is the expectation and variance of $X_t-X_s$? Are $X_t-X_s , X_s$ independent for $s<t$? Is $X_t$ continuous? Levy's Characterization shall do the rest:… Alternately try Ito's Lemma directly. – Alex R. Feb 1 '13 at 0:11

The process $(X_t)_{t\geqslant0}$ is gaussian centered and starts from $X_0=U_0=B_0=0$. For $t\leqslant s$, the covariance of $X_t$ and $X_s$ is $(1+t)(1+s)$ times $$ \mathbb E((B_\tau-\tau B_1)(B_\sigma-\sigma B_1))=\mathbb E(B_\tau B_\sigma)-\tau \mathbb E(B_\sigma B_1)-\sigma \mathbb E(B_\tau B_1)+\tau\sigma\mathbb E(B_1^2), $$ where $\tau=t/(1+t)$ and $\sigma=s/(1+s)$, hence $\tau\leqslant\sigma$. Applying $\mathbb E(B_uB_v)=\min(u,v)$ for every $(u,v)$ to each term yields $$ \mathbb E((B_\tau-\tau B_1)(B_\sigma-\sigma B_1))=\tau-\tau\sigma-\tau\sigma+\tau\sigma=\tau(1-\sigma), $$ hence $$ \mathbb E(X_tX_s)=(1+t)(1+s)\tau(1-\sigma)=t. $$ This proves that the process $(X_t)_{t\geqslant0}$ is a standard Brownian motion.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.